The Future of The Green Economy in Indonesia: Challenges and Opportunities in The Energy Transition - Loso Judijanto; Pramudi Harsono; Olyvia Rosalia (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the challenges and opportunities in Indonesia's transition towards a green economy, with a focus on the shift from fossil fuel dependence to renewable energy. As a developing country with abundant natural resource potential, Indonesia faces significant challenges in reducing greenhouse gas emissions and achieving the Net Zero Emission target by 2060. The study finds that although Indonesia has significant renewable energy potential such as solar, wind, and geothermal energy the development of renewable energy infrastructure and technology remains limited. Additionally, resistance from the fossil fuel industry and energy distribution inequality across regions pose obstacles to the implementation of energy transition policies. However, this transition also offers new economic opportunities, including the creation of green jobs and the growth of the green technology sector. Collaboration among the government, private sector, society, and academia is needed to accelerate the transition towards a sustainable green economy.